Ekonomi Konvensional Vs Ekonomi Islam - Abd Ghafur (Fakultas Ekonomi dan Bisnis Islam, 2017)
When discussing the modern economics system, usvally referring to large systems; capitalis and socialism. Capitalism is a system based on voluntary exchange in a free market. On the contray, socialism trres to unite the problems of production, consumption, and distribution through planning or cominand. On Islamic economics in relation to socialism or capitalism is not bout “wheter” Islamic economics is socralism or capitalism, bot rather to “where” it is in the spectrum, is there any diffence between the two systems. Capitalism economics system, every person is free to own property and one is free to estabilish. Manage the desired enterprise, bcause incapitalist system capital is the source of production and source of freedom. The socialist economics system of all formsof production and source of stateowned commerce, individuals are not permitted to own it. Islamic economic syitem based on the teachings and valves of Islam that the state acts as a policy maker and performs supervisory functions in order to avoid distorsion by the economiy.